Body appreciation is associated with emotional eating in Turkish female athletes - Kenger, E. B.; Karahan, T. O. (International Journal of Sports Medicine, 2024)
It is known that female athletes are at risk for eating disorders. It is thought that factors such as pressure and stress experienced by professional athletes may affect emotional eating and body appreciation. In this context, the aim of this study was to evaluate the emotional eating and body appreciation of professional Turkish female athletes. A total of 265 professional female athletes were categorized according to their sport types and nationality. Emotional eating was found to be higher and body appreciation to be lower in athletes competing at the national level. The results of the hierarchical regression analysis, which included variables such as age, body mass index, professional sports background, national level, and sport type show that the most effective factor in explaining emotional eating in professional female athletes is body appreciation. The present study findings support that professional female athletes are at risk in terms of emotional eating and body appreciation. In addition, emotional eating scores were found to be higher and body appreciation scores were lower in national athletes. Psychological factors such as intense stress and pressure have an impact on the eating behavior and body appreciation of national athletes. These results suggest that athletes should be evaluated by nutritionists, doctors, and psychologists from a multidisciplinary perspective.